Adding Coronary Calcium Score to Exercise Treadmill Test: An Alternative to Refine Coronary Artery Disease Risk Stratification in Patients with Intermediate Risk Chest Pain. Issue 1 (3rd March 2020) - Huang, Weiting; Huang, Zijuan; Koh, Natalie Si Ya; Ho, Jien Sze; Chua, Terrance Siang Jin; Tan, Swee Yaw
Introduction: Chest pain is a common symptom for cardiology referrals. The ACC-AHA guidelines recommend exercise stress electrocardiography (TMX) as the initial diagnostic test. However, the TMX only has moderate sensitivity and non-diagnostic cases may require further stress imaging studies. In this study we aimed to look at the feasibility of combining coronary artery calcium (CAC) score with TMX to refine risk stratification. This may be an alternative to stress imaging in cases of non low-risk TMX, with the added advantage of short time turnaround time and low radiation dose. Methods: A total of 145 patients who presented consecutively to the National Heart Centre Singapore with chest pain were included in this study. These were intermediate risk patients with an average Duke Clinical Score of 38.8%. All patients underwent both TMX and computed tomography scan of the coronary arteries (CTCA) which also includes CAC. The primary outcome was defined as obstructive coronary artery disease i.e. >50% left main artery stenosis and/or >70% stenosis in other epicardial arteries. Results: The combination of TMX and CAC was comparable to stress imaging in detecting obstructive coronary artery disease. When added to TMX, CAC has an integrated discriminative improvement of 74.1%, achieved an area under the curve of 0.974 and adjusted R2 of 0.670 in detecting the primary outcome. Conclusion: The strategy of combining TMX and CAC is feasible in clinical practice to refine risk stratification in outpatients with intermediate risk chest pain. The calcium score readout also further guides therapy for primary prevention. Highlights: Treadmill exercise is one of the first line tests for cardiac chest pain work up. Non diagnostic test treadmill results requires further adjunctive tests. Downstream stress imaging causes delay in time to diagnosis. Coronary artery calcium scoring needs minimal preparation with fast turnaround time. Addition of coronary artery calcium to treadmill performs comparably to stress imaging. This is a feasible alternative to risk stratify non diagnostic treadmill tests and guide therapy for primary prevention.